Re‐evaluation of sucrose esters of fatty acids (E 473) as a food additive in foods for infants below 16 weeks of age and follow‐up of its previous evaluations as food additive for uses in foods for all population groups - EFSA Panel on Food Additives and Flavourings (FAF); Maged Younes; Gabriele Aquilina; Laurence Castle; Gisela Degen; Karl‐Heinz Engel; Paul J Fowler; Maria Jose Frutos Fernandez; Peter Fürst; Rainer Gürtler; Trine Husøy; Melania Manco; et al. (EFSA Journal)
Abstract Sucrose esters of fatty acids (E 473) was re‐evaluated in 2004 by the former EFSA Panel on Food Additives, Flavourings, Processing Aids and Materials in Contact with Food (AFC Panel). In addition, the former EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS Panel) issued scientific opinions on the safety of sucrose esters of fatty acids (E 473) in 2010, 2012 and 2018. As a follow‐up to these assessments, the Panel on Food Additives and Flavourings (FAF) was requested to assess the safety of sucrose esters of fatty acids (E 473) for its uses as food additive in food for infants below 16 weeks of age. In addition, the FAF Panel was requested to address the issues already identified by the EFSA AFC and ANS Panels when used in food for the general population. The process involved the publication of calls for data to allow the interested business operators to provide the requested information to complete the risk assessment. The Panel concluded that the technical data provided by the interested business operators support an amendment of the specifications for sucrose esters of fatty acids (E 473) laid down in Commission Regulation (EU) No 231/2012. According to the available information, E 473 is not used in food categories (FCs) 13.1.1 and 13.1.5.1, including all types of food for infants below 16 weeks of age, and in FC 13.1.5.2. As a consequence, an assessment of the safety for the uses of E 473 as food additive in these FCs and age group was not performed. When the updated exposure estimates considering the provided use levels for some food categories are taken into account the estimates of exposure to sucrose esters of fatty acids (E 473) exceeded the group acceptable daily intake (ADI) of 40 mg/kg body weight (bw) per day for many population groups.